The Effect of Using the Audio-Visual Media “The Origins of Kediri” on the Short Story Writing Skills of Grade XI at SMAN 4 Kediri - Armandasari, Devi; Endang Waryanti; Andri Pitoyo (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Indonesian language learning aims to help students develop language skills through various activities such as reading, writing, speaking, and listening. The use of media can influence students' writing skills. Audio-visual media, especially those based on regional culture and language, can improve students' understanding of the language they are learning. This study also found that the use of the audio-visual media "Asal-Usul Kediri" significantly improved students' language skills. The research design involved a non-equivalent control group to test the effect of the use of the audio-visual media "Asal-Usul Kediri" on student learning achievement. The instrument used in this study was a test, which is an instrument used to collect test data. The statistical tests used in this study were descriptive statistical tests, homogeneity tests, normality tests, and hypothesis tests with the SPSS 29.0 program. The use of the audio-visual learning media "Asal-Usul Kediri" had a positive impact on students' short story writing skills. Based on the conclusions of this study, it is recommended: (1) The use of the audio-visual learning media "Asal-Usul Kediri" can develop students' regional insights. Therefore, teachers as implementers of learning must prioritize processes that support the creation of an educational learning atmosphere. (2) Teachers still need to conduct continuous research to prove that the use of the audio-visual learning media "Origins of Kediri" is appropriate for all the material and characteristics of students.